Borate / phosphate salts based on amine cations, methods for their preparation and use in catalysing the polymerisation of conjugated dienes
Patent Information
- Application Number
- CN202510519032.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
在这样的前提下高活性和具有明确分子结构的硼酸盐助催化剂体系开始被研究和应用,但在现有技术中,合成硼酸盐的反应条件苛刻,反应路线复杂、具有较高的生产成本,该住催化体系对整个聚合过程的调控效果不好,易造成产物分子量过高,使工业生产中产物容易出现粘釜现象
[0053](1)本发明提供的基于胺正离子的硼酸盐/磷酸盐的制备工艺简单,在温和的反应条件下就可实现基于胺正离子硼酸盐/磷酸盐的制备,传统硼酸盐如三苯碳鎓四(五氟苯基)硼酸盐采购价格约为30元/g,在本发明提出的制备方法下新硼酸盐/磷酸盐生产成本可降到0.8元/g,极大节省了硼酸盐制备和后期聚合生产成本。
Smart Images

Figure CN122977978A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of iron-based catalytic olefin polymerization, specifically relating to an amine cation borate / phosphate, its preparation method, and its application in catalytic conjugated diene polymerization. Background Technology
[0002] Rubber is mainly divided into natural rubber and synthetic rubber. The main raw material for natural rubber, Rubber trifoliata, is a tropical plant. The production of natural rubber is limited and cannot meet the demand of tens of millions of tons per year. Therefore, synthetic rubber has become an effective way to solve this problem, which has sparked a frenzy of research.
[0003] The preparation of synthetic rubber requires a suitable cocatalyst system. Methylaluminoxane (MAO) is one of the earliest cocatalysts used in polymerization. However, MAO has certain structural uncertainties. Researchers hope to find a cocatalyst system with a well-defined molecular structure to prepare synthetic rubber, so that the final polymerization product can be verified on a valid theoretical basis. Under this premise, highly active borate cocatalyst systems with well-defined molecular structures have begun to be studied and applied. However, in the current technology, the reaction conditions for synthesizing borates are harsh, the reaction route is complex, and the production cost is high. The current catalytic system has poor control over the entire polymerization process, which can easily lead to excessively high molecular weight products, making the products prone to sticking to the reactor in industrial production. Therefore, developing a new cocatalyst system with mild reaction conditions, simple operation, low cost, good polymerization control effect, and conducive to industrial production has extremely high scientific research value and industrial application value. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a amine cation-based borate / phosphate and its preparation method, which provides more choices and development directions for the polymerization of olefin and terpene monomers. At the same time, it provides the application of amine cation-based borate / phosphate in the catalytic polymerization of conjugated dienes. This borate / phosphate can achieve efficient and controllable homopolymerization or random copolymerization of petroleum-based conjugated dienes and bio-based terpenes.
[0005] The technical solution of the present invention is as follows:
[0006] One objective of this invention is to provide a borate / phosphate structure based on an amine ion with the following general formula:
[0007]
[0008] In the formula, X is F, Cl or Br, and R1, R2 and R3 are each independently selected from the following groups: hydrogen atom, phenyl, C1-C30 straight-chain or non-straight-chain alkyl, C1-C30 substituted straight-chain or substituted non-straight-chain alkyl, C7-C30 substituted aryl, and the total number of carbon atoms in R1, R2 and R3 is ≥10.
[0009] Preferably, the amine-based borate is selected from one of formulas B1 to B12:
[0010]
[0011]
[0012] The amine-based phosphate is selected from one of formulas P1 to P8:
[0013]
[0014]
[0015] A second objective of this invention is to provide a method for preparing the above-mentioned amine cation-based borates / phosphates, wherein the preparation method is carried out according to the following steps:
[0016] S1: Dissolve the corresponding organic amine compound in a suitable organic solvent, add an equimolar amount of hydrochloric acid aqueous solution, and stir for a certain period of time;
[0017] S2: Subsequently, an equimolar amount of aqueous haloborate or hexafluorophosphate solution was added and stirred for a certain period of time. The organic phase was then separated, and the organic solvent was removed by rotary evaporation to obtain borate / phosphate based on amine ions.
[0018] Preferably, the general structural formula of the organic amine compound is:
[0019]
[0020] In the formula, R1, R2, and R3 are each independently selected from the following groups: hydrogen atom, phenyl, C1-C30 straight-chain or non-straight-chain alkyl, C1-C30 substituted straight-chain or substituted non-straight-chain alkyl, C7-C30 substituted aryl, and the total number of carbon atoms in R1, R2, and R3 is ≥10.
[0021] Preferably, the haloborate is one or more of tetrafluoroboric acid, sodium tetrafluoroborate, tetrachloroboric acid, sodium tetrachloroborate, tetrabromoboric acid, or sodium tetrabromoborate.
[0022] Preferably, the organic solvent is one or more selected from n-hexane, cyclohexane, dichloromethane, dichloroethane, diethyl ether, toluene, ethylbenzene, and THF.
[0023] Preferably, the molar ratio of the organic amine compound to hydrochloric acid is (1-3):1. More preferably, the molar ratio of the organic amine compound to hydrochloric acid is 1:1.
[0024] Preferably, the molar ratio of the haloborate or hexafluorophosphate to the organic amine compound is (1-3):1. More preferably, the molar ratio of the haloborate or hexafluorophosphate to the organic amine compound is 1:1.
[0025] Preferably, the stirring time after adding hydrochloric acid in step S1 is >10 min. More preferably, the stirring time after adding hydrochloric acid in step S1 is 20 min.
[0026] Preferably, the reaction temperature in step S2 is 0–50°C, and the reaction time is >10 min. More preferably, the reaction temperature is 25°C, and the reaction time is 20 min.
[0027] A third objective of this invention is to provide an application of the above-mentioned amine cation-based borate / phosphate as a third component in the polymerization of conjugated dienes catalyzed by activated iron catalysts.
[0028] The steps for the iron catalyst-catalyzed polymerization of conjugated dienes are as follows: Under anhydrous and oxygen-free conditions, solvent, conjugated diene monomer, alkyl aluminum, iron catalyst, and the above-mentioned amine cation-based borate / phosphate are added to the reactor. The polymerization reaction is stirred at 0-100°C for 10-120 min. After the reaction is completed, quencher and anti-aging agent are added. After washing, the mixture is vacuum dried to constant weight to obtain the conjugated diene polymer.
[0029] Preferably, the conjugated diene is selected from one or more of petroleum-based conjugated dienes and bio-based terpenes.
[0030] More preferably, the petroleum-based conjugated diene is at least one of 1,3-butadiene and isoprene.
[0031] More preferably, the bio-based terpene is one or more of α-myrcene, β-myrcene, α-farnesene, and β-farnesene. Most preferably, the bio-based terpene is β-myrcene or β-farnesene.
[0032] Preferably, the general structural formula of the iron catalyst is:
[0033]
[0034] Wherein, R4 and R5 are alkyl, alkoxy, nitrogen-containing or sulfur-containing substituents, and X is EHA-, NDA- or acac-, where EHA- is... NDA - for acac- for n is 2 or 3.
[0035] More preferably, the iron catalyst has one of the following structures:
[0036]
[0037] Preferably, the alkylaluminum is one or a mixture of monochlorodiethylaluminum, dichloroethylaluminum, trimethylaluminum, triethylaluminum, tripropylaluminum, tributylaluminum, triisobutylaluminum, triisopropylaluminum, and diisobutylaluminum hydride.
[0038] Preferably, the volume ratio of solvent to monomer is (1-15):1, more preferably, the volume ratio of solvent to monomer is (3-10):1.
[0039] Preferably, the molar ratio of the monomer to the iron element in the iron catalyst is (100-50000):1, more preferably, the molar ratio of the monomer to the iron catalyst is (1000-25000):1.
[0040] Preferably, the molar ratio of boron or phosphorus in the amine cation-based borate / phosphate to iron in the iron catalyst is (0.1-20):1; more preferably, the molar ratio of boron or phosphorus in the amine cation-based borate / phosphate to iron in the iron catalyst is (0.1-5):1.
[0041] Preferably, the molar ratio of aluminum in the alkylaluminum to iron in the iron catalyst is (10-100):1; more preferably, the molar ratio of aluminum in the alkylaluminum to iron in the iron catalyst is (20-40):1.
[0042] Preferably, the reaction temperature is 0–50°C and the reaction time is 30–120 min.
[0043] The fourth objective of this invention is to provide a conjugated diene polymer obtained from the above-mentioned applications, wherein the conjugated diene polymer has a number-average molecular weight of 10,000 to 500,000 g / mol, a molecular weight distribution of 1.5 to 5.0, a molar content of 3,4-structure in petroleum-based conjugated diene polymer units of 50 to 90% and / or a molar content of 1,2-structure of 50 to 70%, a molar content of 3,4-structure in bio-based terpene polymer units of 40 to 70%, and a glass transition temperature range of -80°C to 10°C.
[0044] Preferably, the conjugated diene polymer has a molecular weight distribution of 2.5 to 2.9, the molar content of 3,4-structure in the petroleum-based conjugated diene polymer unit is 64 to 78% and / or the molar content of 1,2-structure is 64 to 67%, the molar content of 3,4-structure in the bio-based terpene polymer unit is 53 to 59%, and the glass transition temperature range is -70°C to -8°C.
[0045] The fifth objective of this invention is to provide a method for the vulcanization of conjugated diene polymers, wherein the method includes:
[0046] Weigh out 100 parts of conjugated diene polymer, 50-150 parts of silica, 1-60 parts of carbon black, 1-3 parts of vulcanizing accelerator, 0.1-12 parts of vulcanizing agent, and 1-10 parts of zinc stearate by mass, mix and knead.
[0047] Preferably, the carbon black is one or more of N234, N324, N330, and N110, the vulcanizing accelerator is one or more of NS, MBT, NOBS, DZ, and TT, and the vulcanizing agent is sulfur.
[0048] The sixth objective of this invention is to provide a vulcanized rubber prepared by the above method, wherein the vulcanized rubber has a tensile strength >16MPa, an elongation at break >300%, a stress at 100% constant elongation >3MPa, a stress at 300% constant elongation >10MPa, and a resilience of 20-35%; the DMA test results of the vulcanized rubber show that the damping temperature range when tanδ >0.3 is above 30℃.
[0049] Preferably, the vulcanized rubber has a tensile strength > 22 MPa, an elongation at break > 400%, a 100% constant elongation stress > 4 MPa, a 300% constant elongation stress > 11 MPa, and a resilience of 24-29%. The vulcanized rubber DMA test results show that the damping temperature range when tanδ > 0.3 can reach up to 39℃.
[0050] The seventh objective of this invention is to provide an application of the vulcanized rubber prepared by the above method in tire manufacturing, noise reduction and damping, and shock absorption.
[0051] Application of conjugated diene rubber materials prepared by the above method in tire manufacturing.
[0052] The significant advantages of this invention compared to existing technologies are:
[0053] (1) The preparation process of amine cation-based borates / phosphates provided by the present invention is simple and can be realized under mild reaction conditions. The purchase price of traditional borates such as triphenylcarbium tetra(pentafluorophenyl) borate is about RMB 30 / g. Under the preparation method proposed in the present invention, the production cost of new borates / phosphates can be reduced to RMB 0.8 / g, which greatly saves the cost of borate preparation and subsequent polymerization production.
[0054] (2) The catalytic system provided by the present invention has high activity. When the ratio of borate / phosphate is only 0.1 equivalent, the monomer conversion rate of the entire polymerization reaction can reach more than 99%. At the same time, the complete conversion of monomer can be achieved under high monomer concentration. Optimization of these two parts can effectively improve the efficiency of industrial production and reduce production costs.
[0055] (3) The catalytic polymerization system provided by the present invention has outstanding polymerization regulation effect, which can control the activity of active species and control and reduce the molecular weight of the product on the original basis. This can effectively improve the post-processing performance of the polymer and meet the needs of mass industrial production. Attached Figure Description
[0056] Figure 1 The isoprene homopolymer of Example 21 1 H NMR spectrum;
[0057] Figure 2 The GPC spectrum of the isoprene homopolymer obtained in Example 21 is shown below.
[0058] Figure 3 The image shows the DSC spectrum of the isoprene homopolymer obtained in Example 21. Detailed Implementation
[0059] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0060] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.
[0061] In this invention, all polymerization reactions are carried out under an inert atmosphere, such as one or more inert atmospheres such as nitrogen, helium, and argon.
[0062] The test method for the damping temperature range in the following embodiments is as follows: the product test heating rate is 1℃ / min, the frequency is 1Hz, the strain is 0.3%, and the sample measurement size is 1×5×20mm.
[0063] Preparation examples of borates based on amine ions
[0064] Example 1: The preparation method of amine cation borates in this example is as follows:
[0065] S1: Dissolve trioctylamine (5.0 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0066] S2: Tetrafluoroboric acid (2 mL, 14 mmol, 1 equiv., 48 vol%) was then added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain the amine cation-based borate, abbreviated as borate B1, with the following structure:
[0067]
[0068] Example 2: The preparation method of amine cation borates in this example is as follows:
[0069] S1: Dissolve tri-nonylamine (5.5 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0070] S2: Tetrafluoroboric acid (2 mL, 14 mmol, 1 equiv., 48 vol%) was then added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain the amine-based borate, abbreviated as borate B2, with the following structure:
[0071]
[0072] Example 3: The preparation method of amine cation borates in this example is as follows:
[0073] S1: Dissolve N,N-di-n-hexadecylaniline (7.1 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL), and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0074] S2: Tetrafluoroboric acid (2 mL, 14 mmol, 1 equiv., 48 vol%) was then added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain the amine cation-based borate, abbreviated as phosphate B3, with the following structure:
[0075]
[0076] Example 4: The preparation method of amine cation borates in this example is as follows:
[0077] S1: Dissolve triisononylamine (5.5 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0078] S2: Tetrafluoroboric acid (2 mL, 14 mmol, 1 equiv., 48 vol%) was then added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain the amine-based borate, abbreviated as borate B4, with the following structure:
[0079]
[0080] Example 5: The preparation method of amine cation borates in this example is as follows:
[0081] S1: Dissolve tridecylamine (6.1 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0082] S2: Tetrafluoroboric acid (2 mL, 14 mmol, 1 equiv., 48 vol%) was then added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain the amine-based borate, abbreviated as borate B5, with the following structure:
[0083]
[0084] Example 6: The preparation method of amine cation borates in this example is as follows:
[0085] S1: Dissolve N-methylhexadecylamine (7.9 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0086] S2: Tetrafluoroboric acid (2 mL, 14 mmol, 1 equiv., 48 vol%) was then added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain the amine-based borate, abbreviated as borate B6, with the following structure:
[0087]
[0088] Example 7: The preparation method of amine cation borates in this example is as follows:
[0089] S1: Dissolve trilauridine (7.3 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0090] S2: Tetrafluoroboric acid (2 mL, 14 mmol, 1 equiv., 48 vol%) was then added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain the amine-based borate, abbreviated as borate B7, with the following structure:
[0091]
[0092] Example 8: The preparation method of amine cation borates in this example is as follows:
[0093] S1: Dissolve tris(2-ethylhexyl)amine (5.0 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL), and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0094] S2: Tetrafluoroboric acid (2 mL, 14 mmol, 1 equiv., 48 vol%) was then added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain the amine-based borate, abbreviated as borate B8, with the following structure:
[0095]
[0096] Example 9: The preparation method of amine cation borates in this example is as follows:
[0097] S1: Dissolve N-methyldidecylamine (4.4 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0098] S2: Tetrachloroboric acid (2.1 g, 14 mmol, 1 equiv.) was then added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain the amine-based borate, abbreviated as borate B9, with the following structure:
[0099]
[0100] Example 10: The preparation method of amine cation borates in this example is as follows:
[0101] S1: Dissolve triisononylamine (5.5 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0102] S2: Tetrachloroboric acid (2.1 g, 14 mmol, 1 equiv.) was then added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain the amine-based borate, abbreviated as borate B10, with the following structure:
[0103]
[0104] Example 11: The preparation method of amine cation borates in this example is as follows:
[0105] S1: Dissolve N,N-di-n-hexadecylaniline (7.1 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL), and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0106] S2: Tetrabromoboric acid (4.6 g, 14 mmol, 1 equiv.) was then added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain the amine-based borate, abbreviated as borate B11, with the following structure:
[0107]
[0108] Example 12: The preparation method of amine cation borates in this example is as follows:
[0109] S1: Dissolve tridecylamine (6.1 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0110] S2: Tetrabromoboric acid (4.6 g, 14 mmol, 1 equiv.) was then added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain the amine-based borate, abbreviated as borate B12, with the following structure:
[0111]
[0112] Example 13: The preparation method of amine cation phosphate in this example is as follows:
[0113] S1: Dissolve trihexylamine (3.8 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0114] S2: Subsequently, hexafluorophosphate (2 g, 14 mmol, 1 equiv.) was added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain a phosphate based on the amine ion, abbreviated as phosphate P1, with the following structure:
[0115]
[0116] Example 14: The preparation method of amine cation phosphate in this example is as follows:
[0117] S1: Dissolve trioctylamine (5.0 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0118] S2: Subsequently, hexafluorophosphate (2 g, 14 mmol, 1 equiv.) was added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain a phosphate based on the amine ion, abbreviated as phosphate P2, with the following structure:
[0119]
[0120] Example 15: The preparation method of amine cation phosphate in this example is as follows:
[0121] S1: Dissolve N,N-di-n-hexadecylaniline (7.1 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL), and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0122] S2: Subsequently, hexafluorophosphate (2 g, 14 mmol, 1 equiv.) was added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain a phosphate based on the amine ion, abbreviated as phosphate P3, with the following structure:
[0123]
[0124] Example 16: The preparation method of amine cation phosphate in this example is as follows:
[0125] S1: Dissolve N,N-hexadecylmethylamine (3.8 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0126] S2: Subsequently, hexafluorophosphate (2 g, 14 mmol, 1 equiv.) was added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain a phosphate based on the amine ion, abbreviated as phosphate P4, with the following structure:
[0127]
[0128] Example 17: The preparation method of amine cation phosphate in this example is as follows:
[0129] S1: Dissolve N-methyldidecylamine (4.4 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0130] S2: Subsequently, hexafluorophosphate (2 g, 14 mmol, 1 equiv.) was added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain a phosphate based on the amine ion, abbreviated as phosphate P5, with the following structure:
[0131]
[0132] Example 18: The preparation method of amine cation phosphate in this example is as follows:
[0133] S1: Dissolve triisononylamine (5.5 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0134] S2: Subsequently, hexafluorophosphate (2 g, 14 mmol, 1 equiv.) was added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain a phosphate based on the amine ion, abbreviated as phosphate P6, with the following structure:
[0135]
[0136] Example 19: The preparation method of amine cation phosphate in this example is as follows:
[0137] S1: Dissolve tridecylamine (6.1 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL) and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0138] S2: Subsequently, hexafluorophosphate (2 g, 14 mmol, 1 equiv.) was added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain a phosphate based on the amine ion, abbreviated as phosphate P7, with the following structure:
[0139]
[0140] Example 20: The preparation method of amine cation phosphate in this example is as follows:
[0141] S1: Dissolve tris(2-ethylhexyl)amine (5.0 g, 14 mmol, 1 equiv.) in dichloromethane (50 mL), and add 18% wt hydrochloric acid aqueous solution (2.4 mL, 14 mmol, 1 equiv.), and stir for 20 min;
[0142] S2: Subsequently, hexafluorophosphate (2 g, 14 mmol, 1 equiv.) was added and the mixture was stirred at 25 °C for 20 min. The organic phase was separated, and the organic solvent was removed by rotary evaporation to obtain a phosphate based on the amine ion, abbreviated as phosphate P8, with the following structure:
[0143]
[0144] Example of preparation by catalytic conjugated diene polymerization
[0145] Examples 21-26 investigate the effects of different borate / phosphate systems on the polymerization of conjugated dienes.
[0146] Example 21:
[0147] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0148] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 21, 50 parts by weight of N324, 70 parts by weight of fumed silica, 1.0 part by weight of vulcanizing agent NS, 1.5 parts by weight of sulfur, and 5 parts by weight of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0149] Example 22:
[0150] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B3 (8.78 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0151] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 22, 50 parts by weight of N324, 70 parts by weight of fumed silica, 1.0 part by weight of vulcanizing agent NS, 1.5 parts by weight of sulfur, and 5 parts by weight of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0152] Example 23:
[0153] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B6 (6.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0154] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 23, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization.
[0155] Example 24:
[0156] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B12 (5.2 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0157] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 24, 50 parts by weight of N324, 70 parts by weight of fumed silica, 1.0 part by weight of vulcanizing agent NS, 1.5 parts by weight of sulfur, and 5 parts by weight of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0158] Example 25:
[0159] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and phosphate P2 (4.8 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0160] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 25, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization treatment.
[0161] Example 26:
[0162] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and phosphate P6 (5.6 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0163] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 26, 50 parts by weight of N324, 70 parts by weight of fumed silica, 1.0 part by weight of vulcanizing agent NS, 1.5 parts by weight of sulfur, and 5 parts by weight of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0164] Examples 21 and 27-28 investigate the effects of different iron catalysts on the polymerization of conjugated dienes.
[0165] Example 27:
[0166] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-6 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0167] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 27, 50 parts by weight of N324, 70 parts by weight of fumed silica, 1.0 part by weight of vulcanizing agent NS, 1.5 parts by weight of sulfur, and 5 parts by weight of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0168] Example 28:
[0169] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-9 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0170] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 28, 50 parts by weight of N324, 70 parts by weight of fumed silica, 1.0 part by weight of vulcanizing agent NS, 1.5 parts by weight of sulfur, and 5 parts by weight of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0171] Examples 21 and 29-30 investigate the effect of monomer addition on polymerization.
[0172] Example 29:
[0173] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 1000 equiv.), triisobutylaluminum (793 mg, 4 mmol, 40 equiv.), iron catalyst Fe-7 (10 mL, 100 μmol, 1 equiv.), and borate B1 (45 mg, 100 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0174] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 29, 50 parts by weight of N324, 70 parts by weight of fumed silica, 1.0 part by weight of vulcanizing agent NS, 1.5 parts by weight of sulfur, and 5 parts by weight of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0175] Example 30:
[0176] Under an argon atmosphere, anhydrous cyclohexane (250 mL), isoprene (25 mL, 250 mmol, 25000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 1000 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0177] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 30, 50 parts by weight of N324, 70 parts by weight of fumed silica, 1.0 part by weight of vulcanizing agent NS, 1.5 parts by weight of sulfur, and 5 parts by weight of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0178] Examples 21 and 31-32 investigate the effect of different reaction temperatures on the polymerization of conjugated dienes.
[0179] Example 31:
[0180] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 0 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0181] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 31, 50 parts by weight of N324, 70 parts by weight of fumed silica, 1.0 part by weight of vulcanizing agent NS, 1.5 parts by weight of sulfur, and 5 parts by weight of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0182] Example 32:
[0183] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 50 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0184] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 32, 50 parts by weight of N324, 70 parts by weight of fumed silica, 1.0 part by weight of vulcanizing agent NS, 1.5 parts by weight of sulfur, and 5 parts by weight of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0185] Examples 21, 33-43 investigate the effects of different polymerizing monomers on iron-based catalytic polymerization.
[0186] Example 33:
[0187] Under an argon atmosphere, anhydrous cyclohexane (89 mL), 1,3-butadiene (8.9 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0188] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 33, 50 parts by weight of N324, 70 parts by weight of fumed silica, 1.0 part by weight of vulcanizing agent NS, 1.5 parts by weight of sulfur, and 5 parts by weight of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0189] Example 34:
[0190] Under an argon atmosphere, anhydrous cyclohexane (173 mL), β-myrcene (17.3 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 500 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0191] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 34, 50 parts by weight of N324, 70 parts by weight of fumed silica, 1.0 part by weight of vulcanizing agent NS, 1.5 parts by weight of sulfur, and 5 parts by weight of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0192] Example 35:
[0193] Under an argon atmosphere, anhydrous cyclohexane (275 mL), β-farnesene (27.5 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 500 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0194] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 35, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization.
[0195] Example 36:
[0196] Under an argon atmosphere, anhydrous cyclohexane (93 mL), isoprene (7 mL, 70 mmol, 7000 equiv.), 1,3-butadiene (2.7 mL, 30 mmol, 3000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain a random copolymer elastomer.
[0197] Preparation of vulcanized rubber: 100 parts by mass of the random copolymer elastomer of Example 36, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate were weighed and mixed and vulcanized to obtain vulcanized rubber.
[0198] Example 37:
[0199] Under an argon atmosphere, anhydrous cyclohexane (120 mL), isoprene (7 mL, 70 mmol, 7000 equiv.), β-myrcene (5.2 mL, 30 mmol, 3000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain a random copolymer elastomer.
[0200] Preparation of vulcanized rubber: 100 parts by mass of the random copolymer elastomer of Example 37, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate were weighed and mixed and vulcanized to obtain vulcanized rubber.
[0201] Example 38:
[0202] Under an argon atmosphere, anhydrous cyclohexane (120 mL), isoprene (9 mL, 90 mmol, 9000 equiv.), β-farnesene (2.8 mL, 10 mmol, 1000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain a random copolymer elastomer.
[0203] Preparation of vulcanized rubber: 100 parts by mass of the random copolymer elastomer of Example 38, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate were weighed and mixed and vulcanized to obtain vulcanized rubber.
[0204] Example 39:
[0205] Under an argon atmosphere, anhydrous cyclohexane (120 mL), 1,3-butadiene (6.2 mL, 70 mmol, 7000 equiv.), β-myrcene (5.2 mL, 30 mmol, 3000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain a random copolymer elastomer.
[0206] Preparation of vulcanized rubber: 100 parts by mass of the random copolymer elastomer of Example 39, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate were weighed and mixed and vulcanized to obtain vulcanized rubber.
[0207] Example 40:
[0208] Under an argon atmosphere, anhydrous cyclohexane (150 mL), 1,3-butadiene (8 mL, 90 mmol, 9000 equiv.), β-farnesene (2.8 mL, 10 mmol, 1000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain a random copolymer elastomer.
[0209] Preparation of vulcanized rubber: 100 parts by mass of the random copolymer elastomer of Example 40, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate were weighed and mixed and vulcanized to obtain vulcanized rubber.
[0210] Example 41:
[0211] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (7 mL, 70 mmol, 7000 equiv.), β-myrcene (2.6 mL, 15 mmol, 1500 equiv.), β-farnesene (4.2 mL, 15 mmol, 1500 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min, and then the reaction was terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the clear liquid, the polymer was washed three times with ethanol, and the resulting polymer was vacuum dried at 40°C to constant weight to obtain a random copolymer elastomer.
[0212] Preparation of vulcanized rubber: 100 parts by mass of the random copolymer elastomer of Example 41, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate were weighed and mixed and vulcanized to obtain vulcanized rubber.
[0213] Example 42:
[0214] Under an argon atmosphere, anhydrous cyclohexane (150 mL), 1,3-butadiene (6.2 mL, 70 mmol, 7000 equiv.), β-myrcene (2.6 mL, 15 mmol, 1500 equiv.), β-farnesene (4.2 mL, 15 mmol, 1500 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain a random copolymer elastomer.
[0215] Preparation of vulcanized rubber: 100 parts by weight of the random copolymer elastomer of Example 42, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate were weighed and mixed and vulcanized to obtain vulcanized rubber.
[0216] Example 43:
[0217] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (3.5 mL, 35 mmol, 3500 equiv.), 1,3-butadiene (3.1 mL, 35 mmol, 3500 equiv.), β-myrcene (2.6 mL, 15 mmol, 1500 equiv.), β-farnesene (4.2 mL, 15 mmol, 1500 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min, and then the reaction was terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the clear liquid, the polymer was washed three times with ethanol, and the resulting polymer was vacuum dried at 40°C to constant weight to obtain a random copolymer elastomer.
[0218] Preparation of vulcanized rubber: 100 parts by weight of the random copolymer elastomer of Example 43, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate were weighed and mixed and vulcanized to obtain vulcanized rubber.
[0219] Examples 21 and 44-45 investigate the effect of different borate addition amounts on the polymerization of conjugated dienes.
[0220] Example 44:
[0221] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (0.5 mg, 1 μmol, 0.1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0222] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 44, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization.
[0223] Example 45:
[0224] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (23 mg, 50 μmol, 5 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0225] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 45, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization.
[0226] Examples 21 and 46 investigate the effect of different solvent addition amounts on the polymerization of conjugated dienes.
[0227] Example 46:
[0228] Under an argon atmosphere, anhydrous cyclohexane (30 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate B1 (4.5 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0229] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 46, 50 parts of N324, 70 parts of fumed silica, 1.0 part of vulcanizing agent NS, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization treatment.
[0230] Comparative Example 1:
[0231] Under an argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (10 mL, 100 mmol, 10000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (1 mL, 10 μmol, 1 equiv.), and borate (9.2 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 120 min, and then the reaction was terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol, and the resulting polymer was vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0232] Preparation of vulcanized rubber: Weigh 100 parts by mass of the elastomer polymer of Comparative Example 1, 50 parts by mass of N324, 70 parts by mass of fumed silica, 1.0 part by mass of vulcanizing agent NS, 1.5 parts by mass of sulfur, and 5 parts by mass of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0233] The chemical formula of the borate used in the comparative example is as follows:
[0234]
[0235] Table 1 Test data of conjugated diene homopolymer elastomer
[0236]
[0237]
[0238] Table 2 Test data of conjugated diene homopolymer elastomers
[0239]
[0240] Table 3 Test data for conjugated diene homopolymer elastomers
[0241]
[0242] Table 4 Test data of conjugated diene homopolymer elastomer
[0243]
[0244] Table 5. Test data for conjugated diene random copolymer elastomers
[0245]
[0246] Table 6 Test data for conjugated diene random copolymer elastomers
[0247]
[0248] Table 7 Test data for conjugated diene random copolymer elastomers
[0249]
[0250] Table 8 Test data for conjugated diene random copolymer elastomers
[0251]
[0252] Table 9 Test data for conjugated diene random copolymer elastomers
[0253]
[0254] Table 10 Test data for conjugated diene random copolymer elastomers
[0255]
[0256] Table 11 Test data of conjugated diene random copolymer elastomer
[0257]
[0258] Table 12 Test data for conjugated diene random copolymer elastomers
[0259]
[0260]
[0261] Note: In Tables 1-12, IP represents isoprene, BD represents butadiene, MY represents myrcene, and FA represents farnesene.
[0262] Table 13 Performance test data of homopolymers and random copolymers of conjugated dienes and bio-based terpenes
[0263]
[0264]
[0265] The above description is merely a preferred embodiment of the present invention. These specific embodiments are different implementations based on the overall concept of the present invention, and the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A borate / phosphate based on an amine ion, characterized in that, The general structural formula is: In the formula, X is F, Cl or Br, and R1, R2 and R3 are each independently selected from the following groups: hydrogen atom, phenyl, C1-C30 straight-chain or non-straight-chain alkyl, C1-C30 substituted straight-chain or substituted non-straight-chain alkyl, C7-C30 substituted aryl, and the total number of carbon atoms in R1, R2 and R3 is ≥10.
2. The borate / phosphate according to claim 1, characterized in that, The borates based on the amine ion are selected from one of formulas B1 to B12: Phosphates based on amine ions are selected from one of formulas P1 to P8:
3. The method for preparing borate / phosphate according to claim 1 or 2, characterized in that, The method described: S1: Dissolve the corresponding organic amine compound in a suitable organic solvent, add an equimolar amount of hydrochloric acid aqueous solution, and stir for a certain period of time; S2: Subsequently, an equimolar amount of aqueous haloborate or hexafluorophosphate solution was added and stirred for a certain period of time. The organic phase was then separated, and the organic solvent was removed by rotary evaporation to obtain borate / phosphate based on amine cations.
4. The method according to claim 3, characterized in that, The general structural formula of the organic amine compound is: In the formula, R1, R2, and R3 are each independently selected from the following groups: hydrogen atom, phenyl, C1-C30 straight-chain or non-straight-chain alkyl, C1-C30 substituted straight-chain or substituted non-straight-chain alkyl, C7-C30 substituted aryl, and the total number of carbon atoms in R1, R2, and R3 is ≥10; the haloborate is one or more of tetrafluoroboric acid, sodium tetrafluoroborate, tetrachloroboric acid, sodium tetrachloroborate, tetrabromoboric acid, or sodium tetrabromoborate; the organic solvent is one or more of n-hexane, cyclohexane, dichloromethane, dichloroethane, diethyl ether, toluene, ethylbenzene, and THF; the molar ratio of organic amine compound to hydrochloric acid is (1-3):1; the molar ratio of haloborate or hexafluorophosphate to organic amine compound is (1-3):1; the stirring time after adding hydrochloric acid in step S1 is >10 min; the reaction temperature in step S2 is 0-50℃; and the reaction time is >10 min.
5. The application of the borate / phosphate as described in claim 1 or 2 as a third component in the polymerization of conjugated dienes catalyzed by activated iron catalysts, characterized in that... The step of catalyzing the polymerization of conjugated dienes with the iron catalyst: Under anhydrous and oxygen-free conditions, solvent, conjugated diene monomer, alkyl aluminum, iron catalyst, and the above-mentioned amine cation-based borate / phosphate were added to the reactor. The polymerization reaction was carried out by stirring at 0–100 °C for 10–120 min. After the reaction was completed, quencher and anti-aging agent were added. After washing, the product was vacuum dried to constant weight to obtain the conjugated diene polymer.
6. The application according to claim 5, characterized in that, The conjugated diene is selected from one or more petroleum-based conjugated dienes and bio-based terpenes; The general structural formula of iron catalysts is: Wherein, R4 and R5 are alkyl, alkoxy, nitrogen-containing or sulfur-containing substituents, and X is EHA-, acac- or NDA-, wherein EHA- is NDA - for acac- for n is 2 or 3. Alkyl aluminum is one or a mixture of one of the following: diethylaluminum monochloro, diethylaluminum dichloro, trimethylaluminum, triethylaluminum, tripropylaluminum, tributylaluminum, triisobutylaluminum, triisopropylaluminum, and diisobutylaluminum hydride.
7. The application according to claim 6, characterized in that, The petroleum-based conjugated diene is at least one of 1,3-butadiene and isoprene; the bio-based terpene is one or more of α-myrcene, β-myrcene, α-farnesene, and β-farnesene; the iron catalyst has one of the following structures:
8. The application according to claim 5, characterized in that, The volume ratio of solvent to monomer is (1-15):1, the molar ratio of monomer to iron in iron catalyst is (100-50000):1, the molar ratio of boron or phosphorus in amine cation-based borates / phosphates to iron in iron catalyst is (0.1-20):1, the molar ratio of aluminum in alkylaluminum to iron in iron catalyst is (10-100):1, the reaction temperature is 0-50℃, and the reaction time is 10-120 min.
9. The application according to claim 8, characterized in that, The volume ratio of solvent to monomer is (3-10):1, the molar ratio of monomer to iron in iron catalyst is (1000-25000):1, the molar ratio of boron or phosphorus in amine cation-based borates / phosphates to iron in iron catalyst is (0.1-5):1, and the molar ratio of aluminum in alkylaluminum to iron in iron catalyst is (20-40):
1.
10. The conjugated diene polymer obtained by the application according to any one of claims 5-9, characterized in that, The conjugated diene polymer has a number-average molecular weight of 10,000 to 500,000 g / mol and a molecular weight distribution of 1.5 to 5.
0. The molar content of 3,4-structure in the petroleum-based conjugated diene polymer unit is 50 to 90% and / or the molar content of 1,2-structure is 50 to 70%. The molar content of 3,4-structure in the bio-based terpene polymer unit is 40 to 70%. The glass transition temperature range is -80℃ to 10℃.
11. The vulcanization method of the conjugated diene polymer according to claim 10, characterized in that, The vulcanization method is as follows: Weigh out 100 parts by weight of conjugated diene polymer, 50-150 parts of silica, 1-60 parts of carbon black, 1-3 parts of vulcanizing accelerator, 0.1-12 parts of vulcanizing agent and 1-10 parts of zinc stearate, mix and knead.
12. The method according to claim 11, characterized in that, The carbon black is one or more of N234, N324, N330, and N110, the vulcanizing accelerator is one or more of NS, MBT, NOBS, DZ, and TT, and the vulcanizing agent is sulfur.
13. The vulcanized rubber obtained by the method of claim 11 or 12, characterized in that, The vulcanized rubber has a tensile strength >16MPa, elongation at break >300%, 100% constant elongation stress >3MPa, 300% constant elongation stress >10MPa, and resilience of 20-35%. The DMA test results of the vulcanized rubber show that the damping temperature range when tanδ>0.3 is above 30℃.
14. The application of the vulcanized rubber of claim 13 in tire manufacturing, noise reduction, damping, and shock absorption.